Performance strengthening model of sharia cooperatives (study on sharia cooperatives in Jambi province) - Zulfina Adriani; Tona Aurora Lubis; Besse Wediawati; Hendriyaldi Hendriyaldi (INOVASI, 2022)
The model for strengthening the Performance of Sharia Cooperatives / BMT in Jambi Province is a model produced to strengthen the performance of Sharia cooperatives which is measured from the non-financial aspect, because so far the performance measurement of Sharia cooperatives is measured from the financial aspect. However, the measurement of performance from the financial aspect has no impact on performance. This study aims to explore transformational leadership, the use of information technology, partnerships can strengthen the performance of Sharia cooperatives, which have been experiencing slow growth. The survey data used were 33 Sharia cooperatives in Jambi Province, Indonesia, using the variance-based SEM modeling, Partial Least Square (PLS). This research produces a model that Transformational leadership and the use of information technology can strengthen the performance of Sharia cooperatives by building internal and external partnerships. The model illustrates that transformational leadership and the use of information technology have a positive and significant effect on strengthening the performance of Sharia cooperatives, but the influence of transformational leadership and the use of information technology has a greater positive and significant effect when strengthening performance through partnerships that are built.